2018
DOI: 10.17645/mac.v6i2.1281
|View full text |Cite
|
Sign up to set email alerts
|

Media Practices and Forced Migration: Trust Online and Offline

Abstract: This article explores the relationship between online and offline practices in the special case of forced migration. By applying a central category in social relations, trust/distrust as developed by Niklas Luhmann, this article contributes to the understanding of forced migration in the digital age. It presupposes that, without a strategy of trust, it would be almost impossible to cope with situations of unfamiliarity and uncertainty. By interviewing refugees, the question is in what contexts the refugee reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…Administrative and locative functions of mobile technologies are described by a number of studies as useful tools for refugees to coordinate pathways through the bureaucracy (Glazebrook, 2004), orient themselves in the city (Kaufmann, 2018), and navigate a range of obstacles on their way to finding a new life (Alencar & Tsagkroni, 2019; Graf, 2018; Veronis, Tabler, & Ahmed, 2018). Syrians make active use of social media apps like Facebook, Youtube, WhatsApp, Google Maps, and Google Translate (AbuJarour, Bergert, Gundlach, Köster, & Krasnova, 2019; Alencar, 2017; Graf, 2018; Kaufmann, 2018). Before coming to Europe, they reported to have used smartphones for several years, but that after arrival they needed to re‐appropriate their devices in order to become familiar with the local information landscapes in their new city (Kaufmann, 2018).…”
Section: The Role Of Mobile Phones For Refugee Resettlementmentioning
confidence: 99%
See 2 more Smart Citations
“…Administrative and locative functions of mobile technologies are described by a number of studies as useful tools for refugees to coordinate pathways through the bureaucracy (Glazebrook, 2004), orient themselves in the city (Kaufmann, 2018), and navigate a range of obstacles on their way to finding a new life (Alencar & Tsagkroni, 2019; Graf, 2018; Veronis, Tabler, & Ahmed, 2018). Syrians make active use of social media apps like Facebook, Youtube, WhatsApp, Google Maps, and Google Translate (AbuJarour, Bergert, Gundlach, Köster, & Krasnova, 2019; Alencar, 2017; Graf, 2018; Kaufmann, 2018). Before coming to Europe, they reported to have used smartphones for several years, but that after arrival they needed to re‐appropriate their devices in order to become familiar with the local information landscapes in their new city (Kaufmann, 2018).…”
Section: The Role Of Mobile Phones For Refugee Resettlementmentioning
confidence: 99%
“…At the same time, the attitude and behavior of the host society toward refugees play an important role in how newcomers adopt mobile phones (Alencar, 2017). Based on refugees' accounts, hostility acts from German people such as shouting at refugees when being asked for information about directions in the city (Graf, 2018, p. 153), or social discrimination experienced by North Korean refugee women in South Korea resulted in a greater reliance on mobile phones for assistance, and as a way to avoid direct interactions with the local community (Kang, Ling, & Chib, 2017). However, research also revealed that the desire to become part of the host culture can foster refugees' use of mobile phones for language and cultural learning (Alencar, 2017; Tudsri & Hebbani, 2015).…”
Section: The Role Of Mobile Phones For Refugee Resettlementmentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, four of the contributions to this issue approach the phenomenon of migration from varied perspectives. Heike Graf's (2018) article "Media Practices and Forced Migration: Trust Online and Offline" examines the use of mobile phones among the recent migrants in Sweden and Germany through the notion of trust derived from the systems theory of Niklas Luhmann. The article suggests that the online sphere, accessible through the phone, helps the migrants connect to and stay in contact with their familiar world from which they are physically removed.…”
Section: Contributionsmentioning
confidence: 99%
“…Ample research has scrutinized refugees' media practices. The "connected migrant" maintaining a "culture of bonds" (Diminescu, 2008) has been the subject of the emerging field of "digital migration studies" (Leurs & Smets, 2018), evaluating ramifications of digital technologies in fleeing, waiting, arriving, and integrating (Alencar, 2018;Gillespie, Osseiran, & Cheesman, 2018;Graf, 2018;Leurs, 2017;Twigt, 2018, Witteborn, 2014a. Within the refugee camp, media experiences have been described as "information precarity" (Wall, Campbell, & Janbek, 2017), and as spaces of instability and uncertainty, where media provide ontological security (Smets, 2018) and are used to manage (im)perceptibility (Witteborn, 2014b).…”
Section: Introductionmentioning
confidence: 99%